Robotics: Science and Systems VIII 2012
DOI: 10.15607/rss.2012.viii.006
|View full text |Cite
|
Sign up to set email alerts
|

M-Width: Stability and Accuracy of Haptic Rendering of Virtual Mass

Abstract: Abstract-In many physical human-robot interaction scenarios, such as haptic virtual environments for training and rehabilitation, it is desirable to carefully control the apparent inertia of a robot. Inertia compensation can be used to mitigate forces felt by the user during free-space motion, and rendering of additional inertia is desired for particular rehabilitation and training procedures. Many factors influence the stability and accuracy of rendering for haptic display of a pure mass, including device mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 12 publications
0
25
0
Order By: Relevance
“…We then support the derived K-width using a discrete model, with which coupled stability can be numerically evaluated [15]- [18]. Our resultant approach is perhaps most similar to Colonnese and Okamura [16], in that we will consider both continuous and discrete models; however, unlike [16], we here claim to find a closed-form passivity constraint.…”
Section: Passivity Resultsmentioning
confidence: 63%
See 4 more Smart Citations
“…We then support the derived K-width using a discrete model, with which coupled stability can be numerically evaluated [15]- [18]. Our resultant approach is perhaps most similar to Colonnese and Okamura [16], in that we will consider both continuous and discrete models; however, unlike [16], we here claim to find a closed-form passivity constraint.…”
Section: Passivity Resultsmentioning
confidence: 63%
“…We then plotted these results in Fig. 4, along with the passivity region defined by (16). From the resultant plot, we observed that our passivity region is contained within each of the coupled stability regions, as should be expected.…”
Section: Passivity Vs Coupled Stabilitymentioning
confidence: 55%
See 3 more Smart Citations